2006
DOI: 10.2193/0091-7648(2006)34[1175:eowwrf]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Wildlife Warning Reflectors for Altering White-Tailed Deer Behavior Along Roadways

Abstract: We evaluated the behavioral responses of white‐tailed deer (Odocoileus virginianus) to 4 colors of wildlife warning reflectors (red, white, blue‐green, and amber) that are purported to reduce the incidence of deer—vehicle collisions. We observed white‐tailed deer behaviors relative to roads before and after installation of wildlife warning reflectors using a forward‐looking infrared camera during 90 observation nights. We concluded that wildlife warning reflectors were ineffective in changing deer behavior suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 6 publications
0
33
0
1
Order By: Relevance
“…In some studies, wildlife warning reflectors were found to have little effect on the roadside behaviour of deer, with little change in the rates of road-kill (Waring et al 1991;D'Angelo et al 2006), whereas in others, deer-vehicle collisions were reduced dramatically (Putmam 1997). For macropods, the effectiveness of both red and white reflectors from two brands (Strieter-Lite and Swareflex) were assessed on captive red kangaroos and red-necked wallabies .…”
Section: Warning Reflectors Acoustic Repellents and Scent Repellentsmentioning
confidence: 99%
“…In some studies, wildlife warning reflectors were found to have little effect on the roadside behaviour of deer, with little change in the rates of road-kill (Waring et al 1991;D'Angelo et al 2006), whereas in others, deer-vehicle collisions were reduced dramatically (Putmam 1997). For macropods, the effectiveness of both red and white reflectors from two brands (Strieter-Lite and Swareflex) were assessed on captive red kangaroos and red-necked wallabies .…”
Section: Warning Reflectors Acoustic Repellents and Scent Repellentsmentioning
confidence: 99%
“…Research has shown that wildlife overpasses and underpasses with fencing have reduced WVCs and enabled large ungulate species (Clevenger and Waltho, 2000;Foster and Humphrey, 1995;Dodd et al, 2007;Mata et al, 2008) and smaller animals (Dodd et al, 2004;Woltz et al, 2008;Mata et al, 2008) to cross roads safely. The use of less permanent measures, such as wildlife signage, is still relatively experimental and their effectiveness is uncertain (Romin and Bissonette, 1996;D'Angelo et al, 2006;Huijser et al, 2007). The next step is to integrate wildlife mitigation research and knowledge early into the road planning process.…”
Section: Introductionmentioning
confidence: 99%
“…Anecdotal or testimonial reports from product manufacturers are usually the only evidence of the effects of wildlife repellents. Independent studies often show that deer habituate to the light and sound stimuli (Ujvári et al 1998(Ujvári et al , 2004D'Angelo et al 2006). Chemical repellents, in particular predator odour repellents, reduce deer browsing damages in field trials (Wagner and Nolte 2001;Kimball et al 2009).…”
Section: Introductionmentioning
confidence: 99%